2020
DOI: 10.3390/jintelligence8010010
|View full text |Cite
|
Sign up to set email alerts
|

Tracking with (Un)Certainty

Abstract: One of the highest ambitions in educational technology is the move towards personalized learning. To this end, computerized adaptive learning (CAL) systems are developed. A popular method to track the development of student ability and item difficulty, in CAL systems, is the Elo Rating System (ERS). The ERS allows for dynamic model parameters by updating key parameters after every response. However, drawbacks of the ERS are that it does not provide standard errors and that it results in rating variance inflati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 33 publications
(39 reference statements)
0
7
0
Order By: Relevance
“…Our third application is to the data of an online learning system Math Garden (Hofman et al., 2020; Klinkenberg et al., 2011), which is a platform for practicing primary school mathematics used widely in the Netherlands. Learners can practice various mathematics skills such as addition, fractions and multiplication using series of exercises that are tailored to the level of their skill.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our third application is to the data of an online learning system Math Garden (Hofman et al., 2020; Klinkenberg et al., 2011), which is a platform for practicing primary school mathematics used widely in the Netherlands. Learners can practice various mathematics skills such as addition, fractions and multiplication using series of exercises that are tailored to the level of their skill.…”
Section: Resultsmentioning
confidence: 99%
“…This is not an innocent activity, as it can potentially change the invariant distribution of the ratings. This is a general phenomenon which seems to have received little attention in other works on rating systems (see Hofman et al., 2020, p. 12). In the context of the urnings, we have that if the choice of players is dependent on the current urnings, then the distribution of the updated urnings is no longer equal to the desired invariant distribution:pfalse(r*false)=false∑boldrfalse∑truer~false∑ifalse∑j > ipZfalse(r*false|truer~,i,j,boldrfalse)pYfalse(truer~false|i,j,boldrfalse)pXfalse(i,jfalse|boldrfalse)pbold-italicπfalse(boldrfalse)pbold-italicπfalse(r*false),where the probability of selecting players i and j depends on the current urnings.…”
Section: Methodsmentioning
confidence: 95%
“…Typically, the items are selected based on the current ratings of the learner and the items in the system. Bolsinova et al (2022) and Hofman et al (2020) demonstrated that not correcting for the adaptive item selection can have detrimental consequences for the ratings. If the difficulty of selected items is matched to the learner's ability, then the variance of the ratings will artificially increase.…”
Section: Adaptive Item Selectionmentioning
confidence: 99%
“…Another issue with these rating systems is that the adaptive item selection potentially influences the invariant distribution and has to be corrected for, as described by Hofman et al . (2020, p. 13), which to our knowledge has not been implemented in the rating systems presented above.…”
Section: Introductionmentioning
confidence: 99%
“…Our third application is to the data of an online learning system Math Garden (Klinkenberg et al, 2011;Hofman et al, 2020), which is a platform for practicing primary school mathematics used widely in the Netherlands. Learners can practice various mathematics skills such as addition, fractions, and multiplication using series of exercises that are tailored to the level of their skill.…”
Section: Math Gardenmentioning
confidence: 99%